Answer: 6
Step-by-step explanation:
Let's start by getting the equation to slope intercept form
First simplify
![y + 1 = 3(2x - 4)\\\\y+1=6x-12](https://tex.z-dn.net/?f=y%20%2B%201%20%3D%203%282x%20-%204%29%5C%5C%5C%5Cy%2B1%3D6x-12)
Then get y by itself
![y+1-1=6x-12-1\\y=6x-13](https://tex.z-dn.net/?f=y%2B1-1%3D6x-12-1%5C%5Cy%3D6x-13)
In slope intercept form y=mx+b, m is the slope
In this case the slope is 6
Answer:
I tried my best to explain it, hope it helps!
Step-by-step explanation:
The answer is A,C,D
I checked and that is the correct answers.
Answer: r= 25/3
Step-by-step explanation:
r-4(r+6)=-49 distribute the 4
r-4r-24=-49 combine like terms
-3r-24=-49 add 24 to both sides
-3r=-25 divide by -3
r= 25/3 answer